THE EFFECT OF ALOEVERA’S STEM COMPOST TOWARD THE GROWTH AND PRODUCT OF ELEUTHERINE AMERICANA MERR ON ULTISOL - Rizki Ari Rahmanda; Elly Mustamir; Dwi Zulfita (Jurnal Sains Pertanian Equator, 2019)
This study aimed to increase the the texture of ultisol with the compost of aloevera’s stem and the results of Eleutherine americana Merr on ultisol. This study began from March 23 to July 12, 2018, The research was carried out on Parit H. Hussein II street, Mutiara Gading D19. The method used in the Completely Randomized Design consisted of 5 treatments, 5 replications and each replication there were 4 plant samples. The treatment is as follows: (l1) 400g / polybag, (l2) 800g / Polybag, (l3) 1200g / polybag, (l4) 1600g / polybag and (l5) 2000g / polybag. The variables observed in this study were the number of leaves per clump (strands), number of tillers per clump (tuber), number of bulbs per clump (tubers), fresh weight of bulbs per plant (g), and dry weight of plants (g). The results showed that giving aloevera’s stem compost could improve ultisol texture, growth and yield of onion plants on ultisol. This study found no best dosage of aloe vera midrib for growth and yield of Eleutherine americana Merr plants on ultisol, but an effective dosage of aloe vera midrib was found on the Eleutherine americana Merr plant which was given a dose of 800 g / polybag.